Effect of layered double hydroxide-graphene oxide modifier composition on characteristics of polyvinylidene fluoride based nanocomposite membranes in the separation of Cu2+ - Kusumawati, Nita; Setiarso, Pirim; Supari Muslim; Sinta Anjas Cahyani; Nafisatus Zakiyah; Kahfi, Ashabul (Communications in Science and Technology, 2024)
This research explored the modified polyvinylidene fluoride (PVDF) nanofiber membranes with a composite of layered double hydroxide (LDH) and graphene oxide (GO) to enhance biofouling resistance. The PVDF/LDH-GO nanocomposite membranes were synthesized via vacuum filtration. FTIR analysis confirmed nanocomposite formation with new peaks indicating the presence of GO and LDH. Variations in the LDH:GO ratio affected the physical, mechanical, and performance properties of the membranes. Based on SEM imaging, the 1:1 LDH: GO ratio exhibited the highest Young's modulus and smallest pore sizes. LDH-GO incorporation increased the mechanical strength, porosity, roughness, hydrophilicity, and pure water permeability of the PVDF membranes. The combination of these factors led to balanced permeability and selectivity values towards Cu2+ solution feeds. LDH-GO was proven effective in modifying the PVDF membrane surface for water treatment and inhibiting biofouling up to 64% against E. coli.